Is hypothyroidism a risk for gall stone disease? a study to assess the association - Watali, Yawar Zahoor; Jain, Rahul; Bali, Rajandeep Singh; Mittal, Ankul (International Surgery Journal, 2017)
Background: Gall stones are one of the most common problems affecting the digestive tract requiring hospitalization. The disease frequently occurs in young, otherwise healthy people with a prevalence of 11-36 % on autopsy report. Thyroid diseases are, arguably, among the commonest endocrine disorders worldwide. In the present study, we have tried to determine an association between gall stone disease, and previously diagnosed and undiagnosed hypothyroidism in patients presenting to our hospital for treatment. The aim of this study was to determine association between gallstones and hypothyroidism and to study the prevalence of previously undiagnosed hypothyroidism in all patients of gallstones. Methods: The study was a hospital based cross sectional, observational study conducted on 200 patients with upper abdominal pain attending the Surgery OPD and Emergency over a period of 1 years. Patients were divided into 2 groups: Case group (100 patients) with gall stones on ultrasound and Control group (100 patients) without gall stones on ultrasound. Thyroid profile along with other biochemical investigations was done and both the groups were compared for the parameters. Results: Both groups were comparable for age and sex of the patients. On considering the thyroid profile of the patients in both the groups we observed that 14% of patients were hypothyroid in case group and 8% of the patients in control group. On comparing the two groups, there was no statistically significant difference in the prevalence of hypothyroidism (p value 0.175) between the two groups. There was a significant difference when serum cholesterol and bilirubin levels were compared between the two groups. 7 patients out of 100 cholelithiasis had Choledocolithiasis too, these patients had significantly raised cholesterol and deranged liver function tests. Conclusions: No significant relation between gallstones and hypothyroidism was found in this study (p value=0.175) and need further evaluation. Among the hypothyroid patients the incidence of gall stones was highest among 51-60 years of age so we recommend that TSH level should be measured for every patient with gallstone disease in this age range.